2019
DOI: 10.1088/1741-2552/ab0328
|View full text |Cite
|
Sign up to set email alerts
|

Feature extraction of four-class motor imagery EEG signals based on functional brain network

Abstract: Objective. A motor-imagery-based brain-computer interface (MI-BCI) provides an alternative way for people to interface with the outside world. However, the classification accuracy of MI signals remains challenging, especially with an increased number of classes and the presence of high variations with data from multiple individual people. This work investigates electroencephalogram (EEG) signal processing techniques, aiming to enhance the classification performance of multiple MI tasks in terms of tackling the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 41 publications
1
62
0
1
Order By: Relevance
“…The region of the tongue MI task network seems to cover a wider region and has a weaker connection than other tasks, because the tongue task would call more brain area compared with other tasks. Ai et al [ 30 ] find tongue task calls more neurons, which strongly supports our findings. According to the electrode position in Figure 6 , the connection of right-hand MI task is concentrated in the 7th-12th channels significantly, which corresponds to the area of the brain activity.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The region of the tongue MI task network seems to cover a wider region and has a weaker connection than other tasks, because the tongue task would call more brain area compared with other tasks. Ai et al [ 30 ] find tongue task calls more neurons, which strongly supports our findings. According to the electrode position in Figure 6 , the connection of right-hand MI task is concentrated in the 7th-12th channels significantly, which corresponds to the area of the brain activity.…”
Section: Resultssupporting
confidence: 93%
“…Yang and Gao [ 29 ] proposed a multivariate weighted ordinal pattern transition (MWOPT) network to analyse the driving fatigue behaviour and obtain high accuracy. Ai et al [ 30 ] constructed a single-layer brain network by canonical correlation analysis and combined CSP and local characteristic-scale decomposition to extract the feature of MI signals. Besides, the multifrequency network, as the single-layer network development, can analyse the system from different perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies reported in the literature focused on sensor-based BCIs. First, raw sensor data are filtered into two groups in this study: 0.1-30 Hz and µ rhythm (8)(9)(10)(11)(12)(13). Table 2 lists the classification success of sensor data for 118 channels.…”
Section: Resultsmentioning
confidence: 99%
“…Alazrai et al [8] reported success in finger movements, Lu et al [9] controlled a vehicle using EEG signals, and Xygonakis et al [10], in 2018, studied four-class motor imagery in the EEG source space and improved its accuracy compared to the sensor data analysis. Qingsong et al [11] analyzed four-task motor imagery in 2019, while Zhang et al [12] reported in 2019 that children can successfully use BCIs.…”
Section: Introductionmentioning
confidence: 99%
“…Ai et al proposed a feature extraction method that combined the features of brain function network and local characteristic-scale decomposition (LCD) together. The good performance of this method was verified on the self-designed real-time BCI robot control and has put forward four classes of dataset [42]. In addition, to measure the complexity of EEG time series, Wang et al proposed a fusion entropy (sample entropy, approximate entropy, and spectral entropy) analysis method for EEG and EOG signals.…”
Section: B Feature Fusion Strategymentioning
confidence: 99%